Hospitalizations of victims of accidents with venomous animals - William Campo Meschial; Beatriz Ferreira Martins; Lúcia Margarete dos Reis; Tanimária da Silva Lira Ballani; Cinthia Lopes Barboza; Magda Lúcia Félix de Oliveira (Rev Rene)
A descriptive study based on data obtained from a toxicological information and assistance center, from 2007 to 2011. This study aimed to characterize hospitalizations of victims of accidents with venomous animals, in order to support the development of preventive and assistance measures. Data were tabulated using the Epi Info 6.04d® program; and the results were presented in tables and figure. 344 hospitalizations were found, with predominance of male patients (58.1%), from 20 to 59 years (56.8%), mostly in the summer (39.0%) spring (27.0%), for snakebites (35.2%). The hospital stay ranged from one to 23 days, with 39.0% of patients hospitalized for two or more days, with two deadly accidents with bees. The profile of the inpatients showed a higher number of cases in the economically active population and in males, the percentage of hospitalizations per animal aggressor differed from morbidity data, giving greater severity of accidents by snakes and bees.